J itegemee (rely on yourself): a multi-phase process of co-creating a personal savings intervention with female sex workers in western Kenya to reduce their HIV risk - Kawango Agot; Jacob Onyango; Marylyn Ochillo; Timothy Omondi Okello; Shantana Carol; Tobias Odwar; Jane Moraa; Sophie Otticha; Redempter Odeny; Nicky Okeyo; Linet Ochieng; Gerald Ochieng; et al. (BMC, 2024)
Abstract Background HIV prevalence among female sex workers (FSW) is significantly higher than among women in the general population. Studies have shown that FSW engage in unprotected sex which provides higher compensation when they face emergency situations. We co-created a savings intervention - Jitegemee (rely on yourself) - with FSW to encourage them to save part of their earnings to withdraw in emergency situations in order to reduce risk. Methods We undertook a five-phase intervention development process between February 2021 and July 2023: 1) qualitative interviews with FSW to identify essential intervention features; 2) pilot trial to assess intervention feasibility; 3) literature review of studies on economic empowerment of FSW; 4) scoring of key components of Phases 1-3 on a scale of 1-5 (1 = definitely exclude, 5 = definitely include), for inclusion in the intervention package; 5) workshops with FSW and other key stakeholders to co-design the intervention. Results In phase 1, nearly all participants (99%) found the intervention acceptable to them and 95% believed it would be acceptable to other FSW. Participants suggested inclusion of financial literacy (75%), savings groups (38%) and goal-setting (24%). In the feasibility assessment, 41% saved, of whom 46% withdrew some savings. Condom use was higher among FSW who withdrew their savings compared to those who did not (χ 2 7.52; p = 0.006). In Phase 3, we identified 14 intervention components. In phase 4, all suggested intervention components scored 4.5 on average. In phase 5, we held 3 workshops with FSW to co-design the intervention, which included instructions for how to save and make withdrawals, financial literacy training, and formation of savings groups. Conclusions A savings intervention for and by FSW was highly acceptable and feasible. Involving end-users in the design process is likely to result in greater economic security among FSW and lower engagement in higher risk transactional sex.